Intention to accept pertussis vaccination among Chinese people older than age 5 - Xuewen Tang; Tingting Tang; Rui Yan; Yang Zhou; Xuan Deng; Hanqing He (Taylor & Francis Group, 2021)
Background: The intention of Chinese people older than age 5 to accept the pertussis vaccination is unknown, which is important for the future design of an effective pertussis vaccination program in China. Method: We conducted a cross-sectional survey among people older than age 5 in China. A 24-item questionnaire was used to explore the determinants of intention to accept a pertussis vaccination, and for children and adolescents (≦15 years old), their guardian was required to help answer the questionnaire on their behalf. Univariate and multivariate logistic regression was used to analyze the influencing factors of intention. Results: A total of 3,041 individuals participated in our survey and 3025 completed the questionnaire, among which 1938 (64.07%) reported a positive intention to be vaccinated. A multiple logistic regression analysis revealed that the main positive factors for the intention to accept pertussis vaccination were younger age (Odd ratio [OR] 0.838, P < .001), higher educational attainment (OR 1.171, P = .002), no hospitalization because of the most recent cough (OR 2.468, P < .001), awareness about pertussis (OR 1.958, P < .001), and consideration of pertussis vaccination to be safe (OR 1.450, P = .026). Conclusion: There is a relatively high level of intention to receive the pertussis vaccine among people older than age 5 in China. Future pertussis vaccination strategies geared at them should consider focusing on middle-aged and older individuals and those with a low education as well as strengthen the promotion of disease characteristics, vaccine effectiveness, and safety.